T-Ordering on Generalized Regular Intuitionistic Fuzzy Matrices (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we study T-ordering on generalized regular intuitionistic fuzzy matrices (IFM) named as k−T-ordering, as a generalization of the T-ordering on intuitionistic fuzzy matrices. Some equivalent conditions for this ordering using generalized inverses are derived. Further, we prove that k −T-ordering is not a partial ordering.
Keywords: Fuzzy Matrix, Intuitionistic Fuzzy Matrices, Partial Ordering, k-Tordering.